Utilizing waste for energy: transforming forestry residues into biodiesel / Shahida Hanum Kamarullah, Wan Noni Afida Ab Manan and Nur Sha’adah Zainuddin - Kamarullah, Shahida Hanum; Ab Manan, Wan Noni Afida; Zainuddin, Nur Sha’adah (Universiti Teknologi MARA, Negeri Sembilan, 2023)
Researchers and innovators are consistently exploring alternative options to lessen our reliance on fossil fuels as part of the search for sustainable energy sources. Producing biodiesel from forestry waste is one of promising options. Apart from only providing biodiversity and carbon sequestration, forests often referred to as the "green lungs" of our planet provide a crucial feedstock for the manufacturing of biodiesel or biofuel, a more environmentally friendly fuel than conventional fossil fuels. A significant amount of waste is produced during forest management and timber harvesting activities in the form of branches, leaves, and other byproducts. The residues are allowed to decompose and release methane and carbon dioxide into the environment. Additionally, the accumulation of these residues might impede ecosystem renewal and raise the risk of forest fires. The natural regeneration of certain plant and tree species may be hindered by the presence of forestry waste on the forest floor. Due to the competitive growth of residue, seedlings frequently struggle to establish themselves.